STRESS AND COPING MECHANISM AMONG PROFESI NERS STUDENTS UNIVERSITAS KLABAT - Angelia Friska Tendean (Fakultas Ilmu Keperawatan Universitas Klabat, 2020)
Stress is a complex problem that occurs in individual and communities, both at home, school, and workplace. Response to stress is known as coping. The present study aimed to identify level of stress among students and to determine the coping mechanism and to identify relation betweeen stress level and coping mechanism among students ners profession in Universitas Klabat. Methodology in this study using a cross-sectional study with decriptive correlation design that was conducted among 80 students ners profession were selected by using probabililty sampling method with consecutive sampling techniques. The results are the majority of respondents were mild stress were 45 respondents (56,3%), and all of respondents (100%) have adaptive coping mechanism. There was statisically significant correlation (p=0.028, r=-0.246*) between stress and coping mechanism among students ners profession at Universitas klabat with coefisien correlation were weak and negative correlation, that means lowest stress will increase adaptive coping mechanism. Recommendation for faculty training students ners profession on adaptive coping, managing stressors and improving supports systems may helpfull for them to effectively deal with various stressors during their educational experience. Keywords: Coping Mechanisme, Ners Profession, Stress